Neighborhood scene - Gordon, John C. (photographer):::Creator::::::::::::
Photograph shows a neighborhood. A low hedge bound by two pillars topped with lamps, perhaps marking the entrance to the driveway of a house, stand at the left of the photograph. A figure is partially visible by the pillar on the left. Tracks are also visible between the pillars. Across the street are trees and houses.